Preoperative Predictors of Death and Sustained Ventricular Tachycardia After Pulmonary Valve Replacement in Patients With Repaired Tetralogy of Fallot Enrolled in the INDICATOR Cohort. Issue 19 (6th November 2018) - Geva, Tal; Mulder, Barbara; Gauvreau, Kimberlee; Babu-Narayan, Sonya V.; Wald, Rachel M.; Hickey, Kelsey; Powell, Andrew J.; Gatzoulis, Michael A.; Valente, Anne Marie
Abstract : Background: Risk factors for adverse clinical outcomes have been identified in patients with repaired tetralogy of Fallot before pulmonary valve replacement (PVR). However, pre-PVR predictors for post-PVR sustained ventricular tachycardia and death have not been identified. Methods: Patients with repaired tetralogy of Fallot enrolled in the INDICATOR cohort (International Multicenter TOF Registry), a 4-center international cohort study, who had a comprehensive preoperative evaluation and subsequently underwent PVR were included. Preprocedural clinical, ECG, cardiovascular magnetic resonance, and postoperative outcome data were analyzed. Cox proportional hazards multivariable regression analysis was used to evaluate factors associated with time from pre-PVR cardiovascular magnetic resonance until the primary outcome: death, aborted sudden cardiac death, or sustained ventricular tachycardia. Results: Of the 452 eligible patients (median age at PVR, 25.8 years), 36 (8%) reached the primary outcome (27 deaths, 2 resuscitated death, and 7 sustained ventricular tachycardia) at a median time after PVR of 6.5 years. Cox proportional hazards regression identified pre-PVR right ventricular ejection fraction <40% (hazard ratio, 2.39; 95% CI, 1.18–4.85; P =0.02), right ventricular mass-to-volume ratio ≥0.45 g/mL (hazard ratio, 4.08; 95% CI, 1.57–10.6; P =0.004), and age at PVR ≥28 years (hazard ratio, 3.10; 95% CI, 1.42–6.78; P =0.005) as outcome predictors. In a subgroup analysis of 230 patients with Doppler data, predicted right ventricular systolic pressure ≥40 mm Hg was associated with the primary outcome (hazard ratio, 3.42; 95% CI, 1.09–10.7; P =0.04). Preoperative predictors of a composite secondary outcome, postoperative arrhythmias and heart failure, included older age at PVR, pre-PVR atrial tachyarrhythmias, and a higher left ventricular end-systolic volume index. Conclusions: In this observational investigation of patients with repaired tetralogy of Fallot, an older age at PVR and pre-PVR right ventricular hypertrophy and dysfunction were predictive of a shorter time to postoperative death and sustained ventricular tachycardia. These findings may inform the timing of PVR if confirmed by prospective clinical trials.